Correlation Between COVID-19 Severity, Body Mass Index and Radiological Hepatic Morphology - Qandeel,Haitham (Sociedad Chilena de Anatomía, 2021)
SUMMARY: Obesity and fatty liver steatosis are already considered metabolic risk factors which may aggravate the severity of COVID-19. This study aims to investigate the correlation between COVID-19 severity, obesity, and liver steatosis and fibrosis. 230 consecutive patients with laboratory-confirmed COVID-19 aged between 15 and 84? years, admitted to a hospital devoted to COVID-19 patients, were enrolled in the study. COVID-19 severity was classified as severe versus non-severe based on admission to ICU. Obesity was assessed by Body Mass Index (BMI). CT-scan was used to check for the liver steatosis. Fibrosis-4 score was calculated. The study was conducted in March-May 2020. Obesity strongly and positively correlated with severe COVID-19 illness r: 0.760 (P<0.001). Hepatic steatosis had rather less of a correlation with COVID-19 severity r: 0.365 (P<0.001). Multivariable-adjusted association between hepatic steatosis or obesity, or both (as exposure) and COVID-19 severity (as the outcome) revealed increased risk of severe COVID-19 illness with obesity (Adjusted model I OR: 465.3, 95 % CI: 21.9-9873.3, P<0.001), with hepatic steatosis (Adjusted model I OR: 5.1, 95 % CI: 1.2-21.0, P<0.025), and with hepatic steatosis among obese patients (Adjusted model I OR: 132, 95 % CI: 10.3-1691.8, P<0.001). Obesity remained the most noticeable factor that strongly correlated with COVID-19 severity, more than liver steatosis. However, the risk to COVID-19 severity was greater in those with both factors: obesity and liver steatosis.